Crizotinib Associated Renal Cysts [CARCs]: incidence and patterns of evolution. Issue 1 (December 2017) - Cameron, Laird; Jiang, Damian; Moodie, Kate; Mitchell, Catherine; Solomon, Benjamin; Parameswaran, Bimal
Abstract Background Novel therapeutic agents recently introduced for the treatment of cancer have several unusual side effects. An increased incidence of renal cystic lesions, often with features concerning for malignancy or infection, has been reported in patients with anaplastic lymphoma kinase (ALK) - rearranged advanced non-small cell lung cancer (NSCLC) treated with Crizotinib. Many of these lesions undergo spontaneous resolution despite developing complex features on imaging. We assess the incidence and patterns of evolution of Crizotinib Associated Renal Cysts [CARCs] at our institute and provide histopathology correlation of their benign nature. Methods A retrospective analysis of renal lesions in computerised tomography (CT) scans of 35 patients with advancedALK -rearranged NSCLC who had been prescribed crizotinib at our institution was performed by three radiologists, who analysed the evolution of these lesions, particularly for pre-defined significant and complex changes. Results Of 26 patients eligible for this analysis, 4 (15%) had cysts at baseline that remained stable on crizotinib treatment while 11(42%) developed significant change in 28 renal cysts. Commonest pattern of cyst evolution was enlargement from baseline followed by spontaneous regression (17/28 lesions) while other patterns noted were stable lesions, regression from baseline and ongoing enlargement. The median maximum size reached was 23 mm (range 9 – 67 mm) after a median of 178 days (160 to 1342) on crizotinib. Complex change occurred in 12 cysts, in 7/26 (27%) patients and within 60 days of starting Crizotinib in 10 cysts. Imaging features were falsely concerning for malignancy or abscess in 4/26 patients. Conclusion Most CARCs resolve spontaneously, or have a benign evolution despite enlargement and other features concerning for malignancy or infection on imaging. This unusual manifestation of chemotherapy should be recognised, particularly by radiologists, so that inappropriate treatment decisions are avoided.